Six new species of Paraleia Tonnoir (Diptera, Mycetophilidae): amphinotic elements at the northern range of the Andes - Oliveira, Sarah Siqueira; de Souza Amorim, Dalton (Zootaxa, 2012)
Paraleia was originally described by Tonnoir for P. fulvescens, known from Australia. More recently, eleven Neotropicalspecies were added to the genus—nine of which are from Chile and southern Argentina, one from Bolivia, and one fromPeru. This distribution pattern is typical of many mycetophilid genera. Six new Neotropical species of Paraleia from theAndean Colombia and Ecuador are herein described. Male terminalia of P. bolivari sp. n., P. denticulata sp. n., P. fumosasp. n., and P. tonnoiri sp. n., as well as female terminalia of P. bolivari sp. n., P. denticulata sp. n., P. fumosa sp. n., P.nidorosa sp. n., P. sharkeyi sp. n., and Paraleia sp. are illustrated. High-resolution photos of wings for all species are presented. An identification key for world species of Paraleia is provided.